To solve the quadratic equation \(x^2 - 6x - 20 = 20\) by completing the square, we can follow these steps:
-
First, move the 20 to the left side of the equation:
\[ x^2 - 6x - 20 - 20 = 0 \]
which simplifies to:
\[ x^2 - 6x - 40 = 0 \]
-
Next, isolate the \(x^2 - 6x\) term:
\[ x^2 - 6x = 40 \]
-
Now, complete the square. Take the coefficient of \(x\) (which is -6), divide it by 2 (resulting in -3), and then square it (resulting in 9). Add 9 to both sides:
\[ x^2 - 6x + 9 = 40 + 9 \]
This simplifies to:
\[ (x - 3)^2 = 49 \]
-
Now, take the square root of both sides:
\[ x - 3 = \pm 7 \]
-
Solve for \(x\):
\[ x - 3 = 7 \quad \Rightarrow \quad x = 10 \]
and
\[ x - 3 = -7 \quad \Rightarrow \quad x = -4 \]
Thus, the solutions to the equation \(x^2 - 6x - 20 = 20\) are:
\[ x = 10, x = -4 \]
This corresponds to the choice:
x=10 , x=−4